2019
DOI: 10.4236/jhrss.2019.72021
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Computer-Mediated Communication and Employee Engagement among Telecommuting Knowledge Workers

Abstract: Virtual teams are increasingly expanding across the workforce facing many challenges to remain competitive. Like traditional "brick-and-mortar" workforces, there may be challenges within virtual teams that affect organizational success such as employee engagement, job satisfaction, commitment, leadership, trust, and knowledge sharing. However, it is uncertain how virtual teams maintain long-term sustainability. This research study brings together two constructs, employee engagement and computer-mediated commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 44 publications
2
26
0
Order By: Relevance
“…Moreover, Catteeuw et al (2007) found engaging employees increased the employees' innovation, creativity, and focus on their work. Tate et al (2019) established attentiveness, expressiveness, and motivation as significant predictors of engagement. Lartey (2021) identified career planning, employee autonomy, and manager recognition as drivers of engagement in small and medium size businesses.…”
Section: Employee Engagementmentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, Catteeuw et al (2007) found engaging employees increased the employees' innovation, creativity, and focus on their work. Tate et al (2019) established attentiveness, expressiveness, and motivation as significant predictors of engagement. Lartey (2021) identified career planning, employee autonomy, and manager recognition as drivers of engagement in small and medium size businesses.…”
Section: Employee Engagementmentioning
confidence: 93%
“…The authors noted by understanding the relationship between personality traits, the employee attitudes, and behaviors likely enables managers to accomplish a better fit between employees and their job. When considering increasing employee engagement or creating teleworking opportunities, Tate et al (2019) suggested emotional analysis approaches to gain a profound understanding of the employee's motivation. In fact, Saks (2006) found that employees differ in their levels of job engagement and organization engagement, as well as the predictors and consequences of each kind of engagement.…”
Section: Employee Engagementmentioning
confidence: 99%
“…This factor also included a variable from work related activities, WR_CHAT, answering the question: "I chat with others while at work." Such inclusion is supported by literature as it suggests the existence of direct communication with others when an employee feels the sense of engagement and trust [39]. Finally, the fourth factor was labelled DISENGAGEMENT because all its questions measured the sense of a negative view of the work environment or negative work performance.…”
Section: Factor Analysismentioning
confidence: 94%
“…The impact has much to say and do with the engagement of the remote knowledge worker in ways yet to be fully understood. What we do know is that the use of computer-mediated communications is gradually changing the social and relational aspects of today's work as well as the engagement of the knowledge workers (Tate, Lartey, & Randall, 2019). What we do not know is just how impactful the changes are in terms of their effect on individual and organizational success, and what can be done to mitigate and/or enhance worker and organizational outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaire included the Ultrecht Work Engagement Scale (UWES-9), a validated instrument for measuring employee engagement created bySchaufeli, Bakker, and Salanova (2006). The computermediated communication indicators were identified from the CMC competency scale created bySpitzberg (2006) based on the previous study and recommendation byTate et al (2019). The three selected indicators came from the main factors identified to drive engagement, namely attentiveness, expressiveness, and motivation.…”
mentioning
confidence: 99%